'Soft barriers' – The impact of school ethos and culture on the inclusion of students with special educational needs in mainstream schools in Ireland. (July 2020) - Keon, David Mc
The use of 'soft barriers' to deter students with special educational needs (SEN) from accessing some schools has been reported in the Irish media. This article investigates the influence of ethos and culture on access to and inclusive practice in mainstream schools in Ireland. Ethos and culture are nebulous concepts yet are integral to how schools operate, how they present themselves and how they are perceived by the public. Findings from a small-scale, qualitative research study are used to illustrate this. In the study, the understandings and attitudes of principals, special education teachers and guidance counsellors in mainstream schools in relation to students with Social, Emotional and Behavioural Difficulties (SEBD) are investigated through the use of questionnaires and semi-structured interviews. In line with international experiences, an argument is presented suggesting that many sections of the education system in Ireland, while seemingly having been irrevocably transformed in response to national policy on inclusion, preserve very traditional structures, organisation and attitudes due to issues of ethos and culture remaining largely unchallenged in the inclusion debate. This phenomenon appears to have greater impact at post-primary level. Cosmetic, surface-level changes impede meaningful, systemic change in terms of access and inclusive practice.